Evaluating English language skills: The role of formative and student-centered assessments in language learning - Ghafar, Zanyar Nathir; Hazaymeh, Omar Mohammad-Ameen Ahmad; Raheem, Bareq Raad; Anjum, Farheen (Journal of Language and Pragmatics Studies, 2025)
This study investigates English language proficiency by examining various assessment strategies, outlining their respective advantages and limitations. It concentrates on established evaluation methods to assess their effectiveness in tracking student progress and informing instructional adjustments. Formative assessments are analyzed to gauge language skills across diverse student populations. Formative assessments, such as classroom observation, interactive discussions, quizzes, and short tests, offer real-time feedback and support adaptive teaching. In contrast, summative assessments, including final exams and comprehensive projects, assess cumulative learning outcomes after instructional periods. The study reveals that formative assessments help educators identify learning gaps and implement targeted interventions. Furthermore, the use of alternative evaluation tools like portfolios, peer assessments, and self-evaluation promotes active engagement and critical reflection among learners. By introducing non-traditional assessment practices, this research highlights the value of student-centered approaches that enhance learner involvement and position students as active contributors to their language development. The adoption of varied assessment techniques ultimately supports a more flexible, responsive, and participatory educational environment.